Cephalothrips (Thysanoptera: Phlaeothripidae) in Iran with two new species and key to species - Alavi, Jalil; Minaei, Kambiz (Zootaxa, 2021)
The genus Cephalothrips Uzel is a weakly defined genus in subfamily Phlaeothripinae with its members apparently living on various dead tissues and the leaves of live plants. Two species, C. bicolor sp. n. and C. corona sp. n., are described from Iran that are remarkable for their bicoloured pattern. An illustrated key is provided for the four species recorded in Iran. Feeding behavior in the genus is discussed briefly.